The Vulnerability of Buildings From the Osijek Database - Pavić, Gordana; Bulajić, Borko; Hadzima-Nyarko, Marijana (Frontiers in Built Environment, 2019)
Estimating of buildings vulnerability is based on a well-organized and detailed database of buildings and their characteristics. Creation of the buildings database of the city Osijek is in progress. This database contains, for each building, information regarding its location, geometric and structural characteristics, materials which were used for structural elements, and other relevant data. This paper presents numerical and statistic values of some characteristics of the buildings from the database. Different methods can be applied for the prediction of damage probability in the field of earthquake risk assessment. With the empirical Macroseismic method and the analytical Capacity Spectrum Method, the vulnerability of the few blocks of buildings, typical for the city Osijek, is estimated. For unreinforced masonry structures with flexible floors, the probability of reaching a certain degree of damage is estimated by the two selected methods, and the obtained results are compared.